THE PROFICIENCY OF PHYSICAL EDUCATION INSTRUCTORS IN FINLAND - Khanturaev, N.A (Educational Research in Universal Sciences, 2023)
This scientific article explores the competence of Physical Education (PE) teachers in Finland, examining the educational system, professional development, and the impact of these factors on the quality of PE instruction. Finland’s education system is renowned for its excellence, and understanding the competence of PE teachers within this context provides valuable insights into the factors contributing to the success of physical education in the country. The study draws upon existing literature, educational policies, and interviews with PE educators to analyze the multifaceted dimensions of teacher competence.